Kondisi Sungai di Indonesia Ditinjau dari Daya Tampung Beban Pencemaran: Studi Literatur - Yura Witsqa Firmansyah; Onny Setiani; Yusniar Hanani Darundiati (Fakultas Teknik, 2021)
The condition of rivers in Indonesia in 2018, 25 rivers were heavily polluted, while in 2019, 38 rivers were heavily polluted . Efforts are needed to determine the carrying capacity of river pollution loads so that they can be used as guidelines for river management. This study aims to provide an overview of the conditions of Indonesia’s rivers through a literature review. This literature review uses 10 articles from the Google Scholar database for the period 2014-2020. The rivers under study do not have a pollution load capacity, namely the Code Yogyakarta river, the Bengawan Solo watershed of the Surakarta and Karanganyar sections, the Brantas river in Malang City, the Kupang river, Pekalongan City, the Mahakam river in East Kalimantan, the Winongo river, Sleman Regency, the section of the Brantas river Kekep-Punden Kota Batu, the segment of the Pesanggrahan river of the City; Garang river, Central Java Bedung river, Denpasar City. Most of the parameters that exceed the loading capacity of the entire river are BOD, COD, TSS, nitrite, nitrate, phosphate, and ammonia. The source of pollution in most rivers is unidentified (certain and uncertain sources of pollution). Generally, river management efforts are not carried out in an optimal manner to maintain water quality and condition .